2017
DOI: 10.11648/j.ijcems.20170305.12
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Caesarean Section Deliveries Among Primigravidae in General Hospital Gboko, Benue State, Nigeria

Abstract: Abstract:The purpose of the study was to assess the prevalence of caesarean-section among primigravida in general hospital Gboko, Benue State, Nigeria. The study was a hospital-based cross-sectional retrospective survey conducted from January 2016-December 2016. The target population comprised all the primigravida within the age of 16-45 who underwent caesarean section in General Hospital Gboko, Benue State, Nigeria. The sample size consisted of 224 patients that met the inclusion criteria of caesarean deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 5 publications
1
8
0
1
Order By: Relevance
“…The current study also reported a higher rate of 81.9% primary C/S as compared to the 68.7% and 67.6% reported on other studies (Chukwu et al, 2017;Geidam et al, 2009). Mothers who had a primary C/S are more likely to have a C/S delivery in future pregnancies as health workers are reluctant to try a vaginal delivery in the case of women with a C/S scar.…”
Section: Discussionsupporting
confidence: 53%
“…The current study also reported a higher rate of 81.9% primary C/S as compared to the 68.7% and 67.6% reported on other studies (Chukwu et al, 2017;Geidam et al, 2009). Mothers who had a primary C/S are more likely to have a C/S delivery in future pregnancies as health workers are reluctant to try a vaginal delivery in the case of women with a C/S scar.…”
Section: Discussionsupporting
confidence: 53%
“…En China continental, un estudio nos muestra que la indicación más común fue el parto por cesárea a petición materna (28,%), seguida de desproporción céfalo pélvica (DCP) (14,1%), sufrimiento fetal (12,5%), cesárea previa (10,3%), presentación deficiente y presentación de nalgas (6,6%), macrosomía (6,1%) y otras indicaciones (22,1%) (9) . Existen diversos factores, entre éstos están la condición médica de la madre, la mala posición del bebé, los embarazos gemelares, la DCP, la presentación pelviana, los oligohidramnios, y la preeclampsia entre otras causas (10) ; también existen factores de naturaleza subjetiva como es el miedo por una mala experiencia de un parto vaginal, o conceptos equivocados sobre los beneficios de la cesárea, o la desinformación sobre los resultados adversos ocasionados por la cesárea (11) , como es el caso de estudios que concluyen que el nacer por cesárea electiva es un factor de riesgo de asma en niños de 2 a 5 años (12) .…”
Section: Introductionunclassified
“…Forty-four of these were included in the meta-analysis, having all reported on CS prevalence [ 21 63 , 65 ]. However, only 31 articles [ 21 24 , 27 , 28 , 30 – 32 , 35 , 37 , 38 , 41 , 42 , 44 – 46 , 48 50 , 55 – 61 , 63 , 64 ] reported the indications or complications of CS and, as such, were included in the narrative synthesis. These are presented in the PRISMA flow diagram (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Almost all included studies (41 [91.1%]) applied cross-sectional study design [ 21 , 22 , 24 28 , 30 57 , 65 ]. Of all the included studies, 27 (60.0%) were conducted in health facilities situated in the southern states [ 21 , 23 25 , 28 , 29 , 32 , 34 , 36 , 38 – 40 , 44 – 47 , 49 – 53 , 56 , 57 , 59 , 60 , 63 , 65 ] while 17 (37.7%) were in health facilities situated in the northern states [ 22 , 26 , 27 , 30 , 31 , 33 , 35 , 37 , 41 – 43 , 48 , 55 , 58 , 61 , 64 ]. Also, 82.2% of the included studies were conducted in public [ 21 38 , 40 , 42 , 44 – 55 , 57 , 58 , 60 – 62 , 64 , 65 ] and 80.0% were conducted in tertiary [ 21 – 40 , 42 , 44 – 47 , 49 55 , 57 , 58 , 60 – 62 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation